Operations management practices of hotels and resorts in rinconada: inputs for the development of operations manual for hospitality and tourism industry and laboratory hotel - Yosores, Nikko Ampongan (San Miguel, Iriga City: University of Saint Anthony, 2022)
Operations management practices of hotels and resorts in rinconada: inputs for the development of operations manual for hospitality and tourism industry and laboratory hotel
Includes bibliographical references.
English
Keywords: hospitality, tourism industry